High-resolution manometry in clinical practice: analysis of esophageal motor function according to Chicago classification - O. A. Storonova; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To analyze the basic esophageal pressure metrics according to Chicago classification v3.0, received at high-resolution manometry and to present the results of clinical application. Summary. Nowadays high-resolution manometry is the most exact hi-tech diagnostic method for esophageal motor function disorders. The changes identified during the investigation are systematized in the Chicago classification v3.0. This relatively new diagnostic method was introduced to clinical application in Russian Federation for the first time in 2011. Vasilenko clinic of internal diseases propedeutics, gastroenterology and hepatology (Sechenov University) accumulated significant experience of high-resolution esophageal manometry of overall 1150 studies. Uniqueness of the method consists in capacity to define integrated quantitative and qualitative metrics of esophageal contractile function and to establish their specific disorders e.g.: change of intrabolus pressure at disorders of esophagogastric junction (EGj) outflow, hypercontractile esophagus, fragmented contractions and weak or failed peristalsis, distal esophageal spasm. Assessment of the type of achalasia subtypes has significant impact on the patients’ treatment choice. Differential diagnosis of belching type, rumination, aerophagy became possible at combined application of high-resolution manometry and impedance measurement. According to anatomical location of the lower esophageal sphincter and crural diaphragm several morphological types of gastro-esophageal junction are defined that determine severity of gastroesophageal reflux disease. Additional provocative tests can be recommended prior to considering anti-reflux surgical treatment that will help to forecast the risk of complications. High-resolution manometry is indicated for patients presenting with dysphagia symptoms, noncoronary chest pain, gastroesophageal reflux disease and other disorders. Conclusion. High-resolution manometry is a fundamental diagnostic test of esophageal motor function disorders. Clinical application of this method significantly expands diagnostic potential and allows to carry out personalized treatment that increases treatment quality.